Consuming a Diet of U.S. Military Food Rations Alters Fecal Microbiota Composition but Does Not Increase Intestinal Permeability (FS07-06-19). (13th June 2019) - Karl, J Philip; Armstrong, Nicholes; McClung, Holly; Rood, Jennifer; Montain, Scott
Abstract: Objectives: Recent studies have reported altered fecal microbiota composition together with increased intestinal permeability (IP) and inflammation in individuals consuming military food rations in austere environments, but could not separate effects of the highly processed, commercially sterile ration-based diets from environmental factors. This study aimed to determine how the U.S. Meal, Ready-to-Eat (MRE) food ration affects fecal microbiota composition and IP. Methods: In this parallel-arm trial, 60 adults (95% male, 18–61 yr) were randomly assigned to consume their usual diet for 31d (CON), or a strictly controlled MRE-only diet for 21d then their usual diet for 10d (MRE). Fecal samples were collected at baseline (BL, days -8–0), and during (INT, days 1–21) and after (POST, days 22–31) the intervention period to measure microbiota composition by 16S rDNA sequencing. On days 0, 10, 21 and 31 IP was measured by dual-sugar absorption test, and circulating markers of bacterial translocation from the gut lumen (LPS-binding protein (LBP)) and inflammation (hsCRP) were measured. Results: During INT, carbohydrate (CON vs MRE: 44% vs 50% energy) and fiber (19 vs 26 g/d) intakes were lower in CON relative to MRE, whereas protein intake was higher (18% vs. 13% energy) ( P  ≤ 0.01). Body weight increased over time in CON, but transiently decreased during INT in MRE ( P  = 0.001). Changes in fecal microbiota composition differed over time between groups ( P  ≤ 0.01), with random forest models discriminating the fecal microbiota of MRE and CON samples during INT with 88% accuracy. The most discriminant genera included multiple bacteria used in food production ( Lactobacillus, Lactococcus, Streptococcus, Leuconostoc) which were less abundant in MRE, and the inflammation-associated genus Sutterella which transiently increased in MRE during INT. IP and hsCRP were both lower (25% and 16%, respectively) in MRE relative to CON on day 21 ( P  < 0.05), but did not differ before or after. LBP did not differ between groups at any time. Conclusions: Findings suggest that a highly processed, commercially sterile MRE-only diet reduces the proportions of diet-derived bacteria in the gut microbiota and does not increase IP or inflammation. Funding Sources: US Army Medical Research and Materiel Command. Authors' views do not reflect official DoD or Army policy.